Generation and functional characterisation of Plasmodium yoelii csp deletion mutants using a microhomology-based CRISPR/Cas9 method. Issue 9 (August 2019) - Xu, Ruixue; Liu, Yanjing; Fan, Ruoxi; Liang, Rui; Yue, Lixia; Liu, Shengfa; Su, Xin-zhuan; Li, Jian
Graphical abstract: Highlights: Plasmodium yoelii can repair CRISPR/Cas9-generated DNA breaks by microhomology-mediated end joining. Size mutants of the central repeat in circumsporozoite surface protein (CSP) were successfully generated. A minimum size of the CSP central repeat region is required for mosquito stage development. Abstract: CRISPR/Cas9 is a powerful genome editing method that has greatly facilitated functional studies in many eukaryotic organisms including malaria parasites. Due to the lack of genes encoding enzymes necessary for the non-homologous end joining DNA repair pathway, genetic manipulation of malaria parasite genomes is generally accomplished through homologous recombination requiring the presence of DNA templates. Recently, an alternative double-strand break repair pathway, microhomology-mediated end joining, was found in the Plasmodium falciparum parasite. Taking advantage of the MMEJ pathway, we developed a MMEJ-based CRISPR/Cas9 (mCRISPR) strategy to efficiently generate multiple mutant parasites simultaneously in genes with repetitive sequences. As a proof of principle, we successfully produced various size mutants in the central repeat region of the Plasmodium yoelii circumsporozoite surface protein without the use of template DNA. Monitoring mixed parasite populations and individual parasites with different sizes of CSP-CRR showed that the CSP-CRR plays a role in the development of mosquito stages, with severe developmental defects in parasites with large deletions in the repeat region. However, the majority of the csp mutant parasite clones grew similarly to the wild type P. yoelii 17XL parasite in mice. This study develops a useful technique to efficiently generate mutant parasites with deletions or insertions, and shows that the CSP-CRR plays a role in parasite development in mosquito.